2017
DOI: 10.1097/md.0000000000008000
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value and potential drug target of phosphatase and tensin homolog in breast cancer patients

Abstract: Our meta-analysis demonstrates that PTEN loss is of particular importance for predicting breast cancer aggressiveness and poor prognosis. PTEN is a potential drug target for the development of individualized treatment in BC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…PTEN is a well-characterized tumor suppressor gene, which antagonizes the phosphoinositol-3-kinase/protein kinase B (PKB or Akt) signaling pathway [ 12 ]. The PTEN gene acts as a tumor suppressor gene in multiple cancers, including breast cancer [ 13 , 14 ], nasopharyngeal carcinoma [ 15 ], renal cell carcinoma [ 16 ], non-small-cell lung cancer [ 17 ], hepatocellular carcinoma [ 18 ], human NK/T-cell lymphoma [ 19 ], and osteosarcoma [ 20 ]. The loss of function of PTEN in tumor cells results in the accumulation of critical cell messengers, which increases Akt phosphorylation and activity and leads to decreased apoptosis and/or increased mitogenic signaling [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is a well-characterized tumor suppressor gene, which antagonizes the phosphoinositol-3-kinase/protein kinase B (PKB or Akt) signaling pathway [ 12 ]. The PTEN gene acts as a tumor suppressor gene in multiple cancers, including breast cancer [ 13 , 14 ], nasopharyngeal carcinoma [ 15 ], renal cell carcinoma [ 16 ], non-small-cell lung cancer [ 17 ], hepatocellular carcinoma [ 18 ], human NK/T-cell lymphoma [ 19 ], and osteosarcoma [ 20 ]. The loss of function of PTEN in tumor cells results in the accumulation of critical cell messengers, which increases Akt phosphorylation and activity and leads to decreased apoptosis and/or increased mitogenic signaling [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is one the most common cancers among women. [ 1 , 2 ] Its incidence and mortality contribute to a major public health problem. [ 3 5 ] It has been estimated that 25.1% new cases of BC and 14.7% deaths from this cancer occurred in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated Burkitt's lymphoma; however, the specific pathogenesis of the disease is not fully understood. Our previous studies found that inhibition of the PI3K pathway can inhibit the proliferation of Burkitt's lymphoma, and abnormal expression of phosphatase and tensin homolog (PTEN) is common in solid tumors, including breast cancer, kidney cancer, esophageal cancer, endometrial cancer (6)(7)(8) and diffuse large B cell lymphoma (12). Therefore, a relationship between PTEN overexpression and the incidence of Burkitt's lymphoma has been indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PTEN has been indicated to negatively regulate the PI3K/AKT signaling pathway. As a negative regulatory factor, PTEN exhibits mutations, deletions, methylation and abnormal activity in solid tumors (6)(7)(8). PTEN is also abnormally expressed in B-cell lymphomas, including diffuse large B-cell lymphoma (9), resulting in the aberrant activation of the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%